INTERVENSI RUSIA TERLIBAT DALAM PROSES RE-UNIFIKASI MOLDOVA DAN RUMANIA - Nasution, Enda Gustrin P; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is a study of diplomacy which discussing about Russia's intervention process Reunification of the territory Moldova and Romania. The collapse of the Soviet Union in late 1980s surfaced a variety of movement due to the policy of political nationalism "Glasnostâ€. The nationalist movement emerged in the region of Moldova is the desire for the Reunification of Moldova with Romania. The process of Reunification Moldova come within the conflict, conflict arises from the region of Transnistria which is located to the East of Moldova who refuses to fears Reunification of Transnistria be minorities if Reunification occurs. War was not inevitable between Moldova and Transnistria Moldova Romania aided and assisted Russia Transnistria and Ukraine can beat Moldova and Transnistria are Defacto independence.In this research, the another uses the nation analysis level which focused on Russian intervention into Moldova region. This research uses a Neo-Realist perspective in internasional relation and uses theory conflict Wese Becker and intervention theory K.J Holsti.Transnistria conflict successfully thwarted an attempt Reunification of Moldova with Romania. Transnistria's independence de facto and Moldova can not embrace back Transnistria region. The power of Russia in Transnistria the cause of Transnistria can not be embraced again by Moldova.Keywords : Reunification, Intervention, Glasnost, Russia, Moldova, Romania, Transnistria